Inhibition of mycelial growth of Fusarium oxysporum f. sp. lycopersici by isolates of Trichoderma spp. - Vilar Fernandes, Ítalo; Perez de Carvalho, Hebe; Perez de Carvalho dos Santos, Ana Carolina; Galvão Chagas, Yuri José (Revista Agrogeoambiental, 2021)
Tomato crops have great economic importance in Brazil and worldwide; however, its economic return is dependent on the control of several diseases, including Fusarium wilt, caused by Fusarium oxysporum f. sp. lycopersici. The control of this disease is usually based on biological products, which are commonly manufactured with antagonist isolates of Trichoderma sp. Therefore, the antagonistic potential of Trichoderma sp. should be better studied against other phytopathogens, thus expanding the biofungicide options on the market. The objective of the present work was to evaluate the antagonistic potential of different isolates of Trichoderma against the in vitro mycelial growth of F. oxysporum f. sp. lycopersici. Four isolates of Trichoderma spp. were tested, three collected in litterfall and one commercial isolate (T. asperellum). The Trichoderma spp. isolates were evaluated for antagonistic potential against F. oxysporum f. sp. lycopersici using the culture pairing technique. The variables evaluated were: mean colony size (MCS), mycelial growth inhibition percentage (MGIP), mycelial growth rate index (MGRI) of phytopathogen, and antagonism of isolates of Trichoderma spp. through a scale of grades. All isolates of Trichoderma spp. tested reduced the in vitro mycelial growth of F. oxysporum f. sp. lycopersici.